A unique twisted rod‐like pattern due to π‐π stacking induced host‐guest self‐assembly. Issue 19 (6th August 2021) - Mukherjee, Madhumita; Mandal, Piyali; Patra, Diptendu; Pal, Dwaipayan; Shunmugam, Raja; Chattopadhyay, Dipankar
Abstract: Here, we reported a unique twisted rod‐like nano‐architecture of as‐synthesized 4‐fluorocinnmaoyl chloride derived polynorbornene (PNORCNF) on the addition of 1‐pyrenemethanol (PM) as a sensing probe. A significant change in the PNORCNF/PM microenvironment's polarity was observed with increasing PM concentration keeping the solvent (THF) unaltered. The change in polarity could be well documented with the morphological changes of the PNORCNF/PM system. We proposed π‐π interaction between PM and cinnamoyl moiety of PNORCNF for this type of well‐controlled hierarchical self‐aggregation. Abstract :